2006
DOI: 10.1158/1078-0432.ccr-05-2057
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of AGR2 Expression in Breast Cancer

Abstract: Purpose:We aimed to evaluate the expression of the human anterior gradient-2 (AGR2) in breast cancer on RNA and protein level and to correlate it with clinicopathologic data, including patient survival. Experimental Design: AGR2 mRNA expression was assessed by reverse transcription-PCR in 25 breast cancer samples and normal tissues. A polyclonal rabbit AGR antiserum was used for immunohistochemistry on 155 clinicopathologically characterized cases. Statistical analyses were applied to test for prognostic and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 23 publications
7
93
2
Order By: Relevance
“…As such, these proteins might have the potential to be putative breast cancer markers. As expected, some well-known breast cancer markers, such as 14-3-3 proteins (Danes et al, 2008), annexins (Cao et al, 2008a), calmodulin (Gallo et al, 2008), anterior gradient homolog 2 (AGR-2) (Zweitzig et al, 2007;Fritzsche et al, 2006), Galectin-1 (Jung et al, 2007) and Rho-associated protein kinase-2 (ROCK2) (Fu et al, 2008b), were also identified in this 2D-DIGE experiment, lending credence to the reliability of early phase biomarker detection using this experimental strategy. Fig.…”
Section: D-dige and Maldi-tof Ms Analysis Of Total Intracellular Prosupporting
confidence: 78%
“…As such, these proteins might have the potential to be putative breast cancer markers. As expected, some well-known breast cancer markers, such as 14-3-3 proteins (Danes et al, 2008), annexins (Cao et al, 2008a), calmodulin (Gallo et al, 2008), anterior gradient homolog 2 (AGR-2) (Zweitzig et al, 2007;Fritzsche et al, 2006), Galectin-1 (Jung et al, 2007) and Rho-associated protein kinase-2 (ROCK2) (Fu et al, 2008b), were also identified in this 2D-DIGE experiment, lending credence to the reliability of early phase biomarker detection using this experimental strategy. Fig.…”
Section: D-dige and Maldi-tof Ms Analysis Of Total Intracellular Prosupporting
confidence: 78%
“…36 In contrast, another reported that increased AGR2 expression was correlated with poorer outcome in prostate cancer. 13 Similar controversy regarding the prognostic value of AGR2 expression has been observed in breast cancer; with AGR2 upregulation associated with favorable prognosis in one study, 37 and with poor prognosis in another independent analysis. 11 Previous studies of PDAC did not identify a correlation between AGR2 expression and prognosis.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, the expression profile was detected in 117 PA tissues of different histological subtypes for the first time. Aberrant AGR2 expression has been reported in primary breast, lung and prostate carcinomas (14)(15)(16)(17). AGR2 overexpression in breast epithelial cell lines results in the development of metastases in an animal model (18).…”
Section: Discussionmentioning
confidence: 99%